Yaws. (September 2015) - Marks, Michael; Lebari, Dornubari; Solomon, Anthony W; Higgins, Stephen P
Yaws is a non-venereal endemic treponemal infection caused by Treponema pallidum sub-species pertenue, a spirochaete bacterium closely related to Treponema pallidum ssp. pallidum, the agent of venereal syphilis. Yaws is a chronic, relapsing disease predominantly affecting children living in certain tropical regions. It spreads by skin-to-skin contact and, like syphilis, occurs in distinct clinical stages. It causes lesions of the skin, mucous membranes and bones which, without treatment, can become chronic and destructive. Treponema pallidum ssp. pertenue, like its sexually-transmitted counterpart, is exquisitely sensitive to penicillin. Infection with yaws or syphilis results in reactive treponemal serology and there is no widely available test to distinguish between these infections. Thus, migration of people from yaws-endemic areas to developed countries may present clinicians with diagnostic dilemmas. We review the epidemiology, clinical presentation and treatment of yaws.